The Effect of Jasmine Aromatherapy on Short-Term Memory Performance - Paryontri, Ramon Ananda; Zakiyah, Lathifatuz (Universitas Muhammadiyah Metro, 2022)
This study aims to see how successful aromatherapy is at improving short-term memory in students at the State Islamic University of Sunan Ampel Surabaya. Participants in the study were 20 participants who were students with short-term memory impairments and had low scores in short-term memory with under 50. A one-group pretest and posttest experimental design was used in this investigation. The non-parametric Wilcoxon statistical test was employed in data analysis to assess the comparison between pretest and posttest scores in determining the intervention's outcome. The intervention improved short-term memory in 20 of the subjects, with short-term memory scores that were above average. The data analysis yielded a Z = - 2.652 value with a significance of p = 0.709 (p = < 0.05). This indicates a difference in participants' short-term memory before and after the intervention. This suggests that people can effectively improve their short-term memory.